2005
DOI: 10.1016/j.lindif.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Impatience and grades: Delay-discount rates correlate negatively with college GPA

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(155 citation statements)
references
References 22 publications
6
140
1
3
Order By: Relevance
“…It seems unlikely that discounting behaviour, as was examined in this study, could predict a large component of variance in a variable that is influenced by so many other factors. Nonetheless, the growing number of studies finding a relationship between discounting behaviour and academic achievement indicate that discounting behaviour is a small but consistent influence on academic success (Kirby, et al, 2005;Silva & Gross, 2004). Furthermore, our finding of a significant association in our adolescent sample between levels of temporal discounting and academic performance confirms that this influence is present both in adolescents of secondary school age as well as in the older samples, consisting of college students, examined in these previous studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It seems unlikely that discounting behaviour, as was examined in this study, could predict a large component of variance in a variable that is influenced by so many other factors. Nonetheless, the growing number of studies finding a relationship between discounting behaviour and academic achievement indicate that discounting behaviour is a small but consistent influence on academic success (Kirby, et al, 2005;Silva & Gross, 2004). Furthermore, our finding of a significant association in our adolescent sample between levels of temporal discounting and academic performance confirms that this influence is present both in adolescents of secondary school age as well as in the older samples, consisting of college students, examined in these previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, this is, as Kirby et al (2005) have noted, still a considerable proportion when all other factors that can influence both discounting and academic achievement are considered.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is clear evidence from multiple studies that higher intelligence is associated with lower delay discounting (meta-analysis by Shamosh & Gray, 2008), and also that discount rate for real, delayed monetary rewards is reliably negatively correlated with college GPA in undergraduates (i.e., lower discounting rates are correlated with higher GPAs), and the relation remains reliable after controlling for SAT scores (Kirby, Winston, & Santiesteban, 2005). Compatible with these results, Harrison et al (2002) found in a sample of Danish participants that individuals with longer investments in education had substantially lower discount rates.…”
Section: Education/social Classmentioning
confidence: 99%
“…Gatchalian, & Bickel, 2007). Furthermore, research indicates that discount rates are negatively correlated with college GPA (Kirby, Winston, & Santiesteban, 2005), long-term financial strategies and/or savings (Joireman, Sprott, & Spangenberg, 2005), performance in a single-player prisoner's dilemma game (Harris & Madden, 2002;Yi, Johnson, & Bickel, 2005), frequency of cooperative choices on group tasks/activities (Critchfield & Atteberry, 2003), and lower levels of risky-choice behavior (Chesson et al, 2006;Dixon, Marley, & Jacobs, 2003;Odum, Madden, Badger, & Bickel, 2000;Petry, 2001b). The breadth of real-world behaviors that differ across individual discount rates highlights the usefulness of the discounting concept in understanding behavioral differences.…”
mentioning
confidence: 99%